GAMBARAN FAKTOR EFISIENSI ANGGARAN DI RSKD IBU DAN ANAK PERTIWI MAKASSAR TAHUN 2022 - Firda Firda; Dian Ekawaty; Mohammad Ardani Samad; Sriyani Windarti (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2024)
Efficiency can be defined as the determination of how to do something, and the ability to carry out tasks properly and precisely without wasting money, time, and energy. This study aims to be able to see what factors can increase the efficiency of a budget at RSKD Ibu and Anak Pertiwi Makassar 2022.This type of research is qualitative with a case study approach. This research was conducted in several rooms of the Director of the Hospital, the Finance Room and the Administration Room of the Mother and Child Hospital Makassar. The number of informants in this study were 4 informants with techniques using interviews, observations, and documentation studies. The data of this research was obtained by going through the process of interviews with informants.